External Shocks and Inflation in Developing Countries Under a Real Exchange Rate Rule - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1992)
This paper shows that the response of inflation to external shocks is very different when the authorities target the real exchange rate than when they follow a fixed exchange rate or a preannounced crawling peg. Specifically, shocks that would have no effect on the steady-state inflation rate under a fixed exchange rate are either inflationary or deflationary under a real exchange rate rule. Moreover, irrespective of the degree of capital mobility, the authorities will find it difficult to mitigate the destabilizing effects of real shocks on the price level by using monetary policy, except possibly in the very short run.